GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI - Agustiningrum, Adri; Indrawati, cicilia dyahsulistyaningrum; Rahmanto, Andre Novi (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2012)
Abstract: Leadership Styles and Work Motivation Toward Employees Performance. The purpose of study are: investigating effect between leadership styles and work motivation toward employees performance. The type of study conducted by the researcher is quantitative research with descriptive method. Sampling technique is by using proportional random sampling technique. While the data collection techniques used are questionnaires and documentation techniques. Data analysis techniques are by using correlation and multiple regression analysis. Key words: Leadership style, work motivation, employees performance.